Navigating care: family information needs and responsibilities in the context of schizophrenia caregiving - Fitryasari, Rizki; Nurlela, Lela; Syadiyah, Hidayatus; Yusuf, Ah; Maliah, Iin; Ambarwati, Galuh Adjeng; Mulud, Zamzaliza Abdul; Diba, Rafidah Farah; Sari, Dianis Wulan (Jurnal Ners, 2024)
Introduction: : Families of schizophrenia patients need   to obtain information from health services about how to care for them. Limited information and understanding of responsibilities in caring are still obstacles to becoming an empowered family in caring for patients with schizophrenia. The study aimed to explore family needs regarding information from health services and family responsibilities when caring for patients with schizophrenia. Methods: This study used a descriptive qualitative design. The study involved families who cared for patients with schizophrenia in Surabaya, Indonesia. Twenty participants were obtained using purposive sampling techniques and the sample size was determined by data saturation. Data were collected using in-depth interviews, field notes and interview question guides. The data were processed with content analysis. Results: The results showed eight themes. Families need information about patient conditions, medication, routine control, and counseling for patient conditions as well as for families. The family describes the responsibilities carried out for the patient as providing support for patient treatment, fulfilling daily needs, helping with social skills, and providing activities in spare time. Conclusions: Adequate information from health services regarding both the patient's condition and family counseling can help to meet the demands of care, which stimulates families to be more empowered to carry out care responsibilities and has an impact on the ability to care better Keywords: counseling, empowerment, family, mental disorder, responsibility, schizophrenia